2021
DOI: 10.1093/jxb/erab051
|View full text |Cite
|
Sign up to set email alerts
|

Natural ultraviolet radiation exposure alters photosynthetic biology and improves recovery from desiccation in a desert moss

Abstract: Plants in dryland ecosystems experience extreme daily and seasonal fluctuations in light, temperature, and water availability. We used an in-situ field experiment to uncover the effects of natural and reduced levels of UV on maximum PSII quantum efficiency (Fv/Fm), relative abundance of photosynthetic pigments and antioxidants, and the transcriptome in the desiccation-tolerant desert moss Syntrichia caninervis. We tested the hypotheses that: (1) S. caninervis plants undergo sustained thermal quenching of light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 133 publications
0
14
0
Order By: Relevance
“…Recently, a study found that ultraviolet light resulted in an increase in desiccation tolerance in Syntrichia caninervis Mitt. [27]. While UV light was not measured in this current study, the pattern of light measures of C3 vs. C1 and C2 translates to more direct light and thus more UV light for C3.…”
Section: Colony Specific Responses and Environmental Associationsmentioning
confidence: 68%
See 1 more Smart Citation
“…Recently, a study found that ultraviolet light resulted in an increase in desiccation tolerance in Syntrichia caninervis Mitt. [27]. While UV light was not measured in this current study, the pattern of light measures of C3 vs. C1 and C2 translates to more direct light and thus more UV light for C3.…”
Section: Colony Specific Responses and Environmental Associationsmentioning
confidence: 68%
“…In fact, few studies have tested for intraspecific differences in desiccation [15] (and references therein). For example, the percentage of canopy openness (exposure) was related with increased male water stress tolerance [24] and UV light was positively associated with tolerance [27]. Identifying and quantifying environmental associations to desiccation tolerance will provide insight into selection drivers or their correlates.…”
Section: Introductionmentioning
confidence: 99%
“…In its natural desert habitat, this species experiences prolonged periods of desiccated quiescence seasonally, where it dissipates excess solar radiation as heat (Ekwealor et al, 2021). Since UV-B radiation varies substantially seasonally, relative to other regions of the spectrum (Robson et al, 2019), UV-B can act as a phenological cue for plants.…”
Section: Discussionmentioning
confidence: 99%
“…As this protein is uncharacterized, the role it is playing in UVR response can only be speculated upon, but given the high level of desiccation tolerance in this species, the functional annotation is intriguing. In fact, UVR has been implicated in desiccation tolerance in S. caninervis, where removal of natural levels of UVR from a field setting hindered recovery of photosynthetic efficiency from desiccation (Ekwealor et al, 2021). By T 30 , abundance of this transcript had increased again to nearly an LFC of −1 (Figure 4).…”
Section: Differentially Abundant Transcripts With 10 and 30 Min Of Ultraviolet Radiationmentioning
confidence: 99%
See 1 more Smart Citation